The Tradition of “Uang Hantaran” in Riau Malay Marriage: an ”˜Urf-Based and MaqÄá¹£id Al-SharÄ«”˜ah Analysis - Mawardi Mawardi; Masduki Masduki; Khairil Anwar; Firman Surya Putra; Azzuhri Al-Bajuri; Agusman Saputra (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
This study examines the tradition of uang hantaran in Riau Malay marriages from the perspective of Islamic law, addressing the limited analytical discussion on its legal status and socio-religious implications. Using a qualitative ethnographic approach, data were collected through fieldwork in Siak Regency, Pekanbaru City, and Dumai City, involving interviews with community members and religious figures. The findings show that uang hantaran is a deeply rooted customary practice determined through mutual agreement, functioning as both financial support for wedding expenses and a symbol of commitment. However, excessive demands may generate financial burdens, indebtedness, and delays in marriage. From the standpoint of Islamic jurisprudence, although not prescribed in the Qur’an or Sunnah, the practice may be accommodated under the concept of ”˜urf (custom) as long as it aligns with Islamic principles””permissible when it promotes maá¹£laá¸¥ah and invalid when it leads to mafsadah. This study contributes by offering an integrative ”˜urf-based analysis that bridges local cultural practices with Islamic legal theory, providing a more nuanced framework for evaluating customary marriage traditions in contemporary Muslim societies.